Modular Design of Professional Training Programs for Special Education Teachers: Criteria-Based Approach - Tatyana S. Nikandrova; Elena S. Tusheva; Ksenia B. Vovnenko (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
The article features a new training model for special education teachers: the authors developed a set of criteria to link the modern requirements for a special education teacher with the skills acquired in the process of professional training. The first stage involved an expert assessment of special education teachers’ curricula for compliance with the unified requirements of the national teacher’s training model. It covered 36 Russian pedagogical universities that train special education teachers. The curricula were checked for compliance with the unified requirements for modular and distributed structuring of pedagogical education. The second stage yielded the criteria aimed at intensifying the processes of differentiation in special education teachers’ training. The criteria were formulated as a list of statements. Fundamental knowledge correlates with professional knowledge. The education programs for special education teachers have a distinct modular design. They consider the activities stipulated by the professional standard for Special Education (defectologist). Profile training differs from advanced specialization. Research skills are obligatory: theory and practice go hand in hand. The Russian language needs a more important status in the special education teachers’ training, with linguistic practices in Russian. A special education teacher knows the nature and mechanisms of dysontogenesis. A unified assessment approach covers human, spiritual, moral, and patriotic values, as well as such competencies as social responsibility, technologic efficiency, readiness for teaching, enhancing the education potential of the family, etc. Each criterion was provided with a rationale of modular design. The criteria may help to develop more effective education programs for special education teachers.